Malaysia in transition - Chowdhury, Anis (The Philippine Review of Business and Economics, 1996)
The Malaysian economy has undergone rapid transformation within a short span of two decades and has a vision to become a fully developed economy by the year 2020. This paper provides a brief synopsis of this remarkable growth and structural change within Malaysia's historical and political development. It also highlights the problems associated with rapid transformation. The paper argues that the spectacular transformation of the economy cannot be explained by the conventional wisdom of either neo-classical variety or statist paradigm. The paper attributes much of Malaysia's success to its racial compact at the time of independence and the subsequent pursuit of the New Economic Policy which aimed at racial and political harmony within the context of a growing economy. How successfully Malaysia can move toward an "innovation driven" society will depend very much on its success at political reforms toward a more open and plural system.